2016
DOI: 10.1097/wnr.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lactate dehydrogenase A compromises tumor progression by downregulation of the Warburg effect in glioblastoma

Abstract: Reprogrammed glucose metabolism is an emerging hallmark of cancer cells, which show a unique metabolic phenotype known as the Warburg effect. Lactate dehydrogenase A (LDHA), a key enzyme in the glycolytic process, executes the final step by conversion of lactate into pyruvate. However, little is known about the roles of LDHA in human glioblastoma (GBM). In this study, we aimed to determine the effects of LDHA and elucidate related underlying mechanisms. Data derived from Oncomine database showed that LDHA is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16). Consistent with previous studies, our results showed that there was a significant positive correlation between LDHA expression levels and GBM clinical stages.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16). Consistent with previous studies, our results showed that there was a significant positive correlation between LDHA expression levels and GBM clinical stages.…”
Section: Discussionsupporting
confidence: 81%
“…Although the abnormal expression of LDHA has been reported in several cancers (10)(11)(12)(13)(14)(15), little is known about the expression pattern of LDHA and its underlying roles in GBM. Previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to matched tissues (16); these finding prompted us to examine the underlying role of LDHA in glioma malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Lactate dehydrogenase A (LDHA) that converts pyruvate to lactate (and an important component of poor prognostic metabolic subtype 3) and the MCTs that transport lactate and/or pyruvate (SLC16A3 and SLC16A8) across the plasma membrane were part of this signature. LDHA overexpression in solid tumors including gliomas has been implicated in tumor progression, immune evasion, and reduced survival in solid tumors including gliomas (41)(42)(43)(44). Intriguingly, there is evidence of a sexual dimorphism in LDHA expression in both serum and tissue samples in healthy animals (45,46).…”
Section: Glycolytic Gene Expression Stratifies Risk In Gliomasmentioning
confidence: 94%
“…4 During aerobic glycolysis, lactate dehydrogenase-A (LDHA) preferentially metabolizes pyruvate to lactate. 4 During aerobic glycolysis, lactate dehydrogenase-A (LDHA) preferentially metabolizes pyruvate to lactate.…”
Section: Introductionmentioning
confidence: 99%